Does intubation while observing the glottis with a fiberoptic scope reduce postoperative sore throat? - Maho Goto; Masanori Tsukamoto; Kazuya Matsuo; Takeshi Yokoyama (BMC Anesthesiology)
Abstract Introduction In oral maxillofacial surgery, the nasal tracheal tube is mostly used to provide a better surgical field for oral, head and neck operations. Postoperative sore throat and hoarseness are common following tracheal intubation, with an incidence of 11–55%. Then, we previously reported advantage technique of fiberoptic scope to decrease the risk which the tip of the tube is visualized as the tube is advanced which helps avoid impingement of the tube. However, the extent to which this technique causes postoperative complications is unknown compared to traditional technique. The aim of this study was retrospectively to determine the effect of postoperative sore throat following nasotracheal intubation by tip of the tube is visualized by fiberoptic scope. Method Anesthesia records of the adult patients with nasotracheal intubation were checked. Patients underwent oral maxillofacial surgery from January 2021 until March 2023. Facilitated with rocuronium, nasotracheal intubation was performed using the traditional or observative method by fiberoptic scope with a 4.8 mm outer diameter. Intubation was performed with a cuffed 6.5–8.0 mm ID nasotracheal tube. The following variables were recorded: gender, age, height, weight, ASA classification, anesthesia time, duration of intubation, tube size, intubation attempts, fentanyl and remifentanil. The postoperative sore throat and the incidence of hoarseness were recorded at operative day and at the day after operative day, and the time to recovery. Result A total of 104 cases (traditional fiberoptic intubation n = 51, observative fiberoptic intubation n = 53) were enrolled in this retrospective study. There were no significant differences in clinical characteristics and anesthetic data. There was not significant difference in incidence of postoperative sore throat, hoarseness and recovery between the two groups (P = 0.61, 0.44, 0.90). For subjects reporting postoperative sore throat (n = 30), there was not a significant difference in VAS means at operative day and at the day after operative day between the two groups (P = 0.81, 0.91). Conclusion We found that postoperative sore throat and recovery were not influenced by observative fiberoptic scope for nasotracheal intubation.